The Effect of Lecturer Competence and Learning Motivation on Student Learning Achievement in Web Design Subjects (Case Study of Office Administration Education Students, State University of Jakarta) - Cecilia Azhara Ayuningtiyas; Christian Wiradendi Wolor; Darma Rika Swaramarinda, (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
The competence of a lecturer is one of the important role holders in improving student learning achievement from the external side. Problems such as decreased student achievement will arise if the lecturer cannot fulfill his competence in the learning process. In addition, improving student achievement is also inseparable from learning motivation as an internal factor that affects it. This study aims to determine whether lecturer competence and student learning motivation can have an influence on improving student achievement, especially students of the State University of Jakarta Office Administration Education Study Program in Web Design Subjects. In this study using quantitative methods which make numerical data as a research tool through distributing questionnaires with a research sample of 63 respondents. The SPSS version 27 application is the application that will be used for data processing in this study. The test results of this study suggest that learning motivation and lecturer competence have a significant positive impact on learning achievement. Furthermore, the combination of lecturer competence and learning motivation has a significant positive impact on the achievement of learning.